THE IMPACT OF VIDEO-ON-DEMAND SERVICES ON DIGITAL PIRACY: EXPLORING USER SATISFACTION AND SYSTEM FEATURES (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This study explores how the emergence of legal distribution channels affects digital piracy. We use online video-on-demand services as a proxy for legal distribution channels and investigate how increased satisfaction with this service influences the consumption of pirated content. Data for this study were collected through an online survey of a representative sample of 332 participants and analyzed using the Structural Equation Modeling approach. The findings indicate that greater use of subscription-based video-on-demand services significantly reduces the consumption of pirated video content. Additionally, system features such as content richness, system quality, and recommendation mechanisms are crucial in shaping user satisfaction with such services. Based on these findings, this study recommends streaming service providers and policymakers to further promote legal digital consumption and reduce piracy.
Keywords: digital piracy; Structural Equations Model; Technology Acceptance Model; Uzbekistan; video-on-demand services